2020
DOI: 10.1002/lary.28845
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Psychologic Burden on Surgical Outcome in Empty Nose Syndrome

Abstract: Objectives /Hypothesis Empty nose syndrome (ENS) is a complicated condition currently thought to be caused by excessive surgical resection of turbinate tissue. Patients with ENS experienced significant psychological symptoms, such as depression and anxiety. This study aimed to evaluate the impact of the psychological burden on the surgical outcome of ENS. Study Design Prospective case series in a tertiary medical center. Methods Patients with ENS were prospectively recruited between 2015 and 2018. Validated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(53 citation statements)
references
References 27 publications
4
49
0
Order By: Relevance
“…Our previous study also revealed that the ENS symptom domain in the SNOT-25 are associated with psychological burden and could be good predictors of moderate-to-severe depression. 12,16 The current study further demonstrated that the symptom of "Nose feels too open" may associate with suicidal thoughts. Our previous study 12 revealed sleep dysfunction and empty nose symptoms contribute to the psychological burden experienced by ENS patients.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Our previous study also revealed that the ENS symptom domain in the SNOT-25 are associated with psychological burden and could be good predictors of moderate-to-severe depression. 12,16 The current study further demonstrated that the symptom of "Nose feels too open" may associate with suicidal thoughts. Our previous study 12 revealed sleep dysfunction and empty nose symptoms contribute to the psychological burden experienced by ENS patients.…”
Section: Discussionsupporting
confidence: 66%
“…Patients with ENS carry a significant psychological burden including depression and anxiety. 9,11,12,16,21 In the present study, we investigated the suicidal thoughts in ENS patients using validated "Nose feels too open" was the item in ENS6Q that was significantly more severe in ENS patients with suicidal thoughts than those without. This symptom may be the most devastating, mentally, and psychologically to patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations